2015
DOI: 10.1051/0004-6361/201423509
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the secondary eclipse of WASP-10b in theKs-band

Abstract: Context. WASP-10b, a non-inflated hot Jupiter, was discovered around a K-dwarf in a near circular orbit (∼0.06). Since its discovery in 2009, different published parameters for this system have led to a discussion about the size, density, and eccentricity of this exoplanet. Aims. In order to test the hypothesis of a circular orbit for WASP-10b, we observed its secondary eclipse in the Ks-band, where the contribution of planetary light is high enough to be detected from the ground. Methods. Observations were pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
1
15
2
Order By: Relevance
“…Our new orbital eccentricity of e = 0.0589 +0.0033 −0.0026 differs from our previous value by 4σ; this change can be attributed to the inclusion of our measured secondary eclipse times in the new fits as well as the switch to a curved radial velocity trend model. We note that a previous study reported a detection of the secondary eclipse for this planet in the Ks band at an orbital phase of 0.4972 ± 0.0005 (Cruz et al 2015); this offset differs significantly from that of our Spitzer secondary eclipse observations and is also inconsistent with the current radial velocity measurements for this system. The authors of this study note that their reported error is likely an underestimate as it does not account for additional uncertainties contributed by the removal of systematic noise sources from their light curve.…”
Section: Eclipse Model and Uncertainty Estimatescontrasting
confidence: 99%
See 1 more Smart Citation
“…Our new orbital eccentricity of e = 0.0589 +0.0033 −0.0026 differs from our previous value by 4σ; this change can be attributed to the inclusion of our measured secondary eclipse times in the new fits as well as the switch to a curved radial velocity trend model. We note that a previous study reported a detection of the secondary eclipse for this planet in the Ks band at an orbital phase of 0.4972 ± 0.0005 (Cruz et al 2015); this offset differs significantly from that of our Spitzer secondary eclipse observations and is also inconsistent with the current radial velocity measurements for this system. The authors of this study note that their reported error is likely an underestimate as it does not account for additional uncertainties contributed by the removal of systematic noise sources from their light curve.…”
Section: Eclipse Model and Uncertainty Estimatescontrasting
confidence: 99%
“…It is also by far the most massive planet in our sample, a fact that we discuss in more detail below. Although we do not show it in these plots, there is a published Ks (2.1 µm) secondary eclipse measurement available for this planet with a value of 0.137% ± 0.016% (Cruz et al 2015). The measured planet-star flux ratio in this bandpass is 3 − 10× larger than the predictions of our models, and the reported center of eclipse phase differs from our measurement by 2.4 hours (54σ), comparable to the eclipse duration.…”
Section: Day-night Circulationcontrasting
confidence: 67%
“…This survey has already confirmed the A&A 576, A88 (2015) planetary nature of Kepler-91b (KOI-2133b, Lillo-Box et al 2014c, Kepler-432b (KOI-1299b, Ciceri et al 2015, and Kepler-447b (KOI-1800b; and has detected the secondary eclipse of WASP-10b (Cruz et al 2015). In the present paper, we analyze 13 specific candidates in our sample that have shown either large RV variations or broadened spectra owing to the fast rotation of the host stars.…”
Section: Introductionmentioning
confidence: 71%
“…−131 K (Cruz et al 2015). The maximum expected equilibrium temperature for the planet, assuming zero Bond albedo and instant reradiation (A B = 0 and f = 2/3, respectively) is T eq 1224 K. This temperature is about 25% cooler than the observed T Ks .…”
Section: Estimated Thermal Emissionmentioning
confidence: 76%
“…We fit for these systematics simultaneously by performing a multiple linear regression, where we modeled the trends only on the out-of-eclipse portions of the light curve, applied the model to the in-eclipse portion, and removed it from the light curve. The complete description of the reduction procedure and analysis performed can be found in Cruz et al (2015).…”
Section: The Case Study: Wasp-10bmentioning
confidence: 99%